2006
DOI: 10.1096/fj.05-5010fje
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor/CCN2 stimulates actin disassembly through Akt/protein kinase B‐mediated phosphorylation and cytoplasmic translocation of p27Kip‐1

Abstract: Connective tissue growth factor (CTGF/CCN2) is a 38-kDa secreted protein, a prototypic member of the CCN family, which is up-regulated in many diseases, including atherosclerosis, pulmonary fibrosis, and diabetic nephropathy. We previously showed that CTGF can cause actin disassembly with concurrent down-regulation of the small GTPase Rho A and proposed an integrated signaling network connecting focal adhesion dissolution and actin disassembly with cell polarization and migration. Here, we further delineate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…In fact, it was reported that CCN2 adversely affected actin polymerization through the Rho signaling pathways (Crean et al 2006), which may form a negative feed back loop for CCN2 production …”
Section: Discussionmentioning
confidence: 99%
“…In fact, it was reported that CCN2 adversely affected actin polymerization through the Rho signaling pathways (Crean et al 2006), which may form a negative feed back loop for CCN2 production …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we found increased expression of the p27 cyclin-dependent kinase inhibitor following Nf1 inactivation in CTX NSCs, but not in BS NSCs. p27 function is regulated by Akt-mediated phosphorylation at residues Thr 198 and Ser 10, resulting in cytoplasmic localization and inhibition of its activity (Fujita et al 2002;Motti et al 2004;Crean et al 2006). Akt also regulates Skp2 (S-phase kinase-associated protein-2), a SCF F-box protein, which binds to p27 and targets it for ubiquitination and degradation (Lin et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, biglycan, which was shown to be regulated by TGF-␤, may itself be protective since this proteoglycan was reported to enhance the survival of neurons (33,35). CTGF, which is expressed secondarily to TGF-␤ and angiotensin II in the heart post-MI, signals through Akt similarly to WISP-1 (20,55). However, CTGF has been shown to induce apoptosis in several cell types, including human aortic smooth muscle (30) and peritoneal mesothelial cells (53).…”
Section: Discussionmentioning
confidence: 99%